2007
DOI: 10.1118/1.2760027
|View full text |Cite
|
Sign up to set email alerts
|

IMRT optimization including random and systematic geometric errors based on the expectation of TCP and NTCP

Abstract: The purpose of this work was the development of a probabilistic planning method with biological cost functions that does not require the definition of margins. Geometrical uncertainties were integrated in tumor control probability (TCP) and normal tissue complication probability (NTCP) objective functions for inverse planning. For efficiency reasons random errors were included by blurring the dose distribution and systematic errors by shifting structures with respect to the dose. Treatment plans were made for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 52 publications
1
57
0
Order By: Relevance
“…The 3 mm random setup uncertainty is representative of those used in related literature 4,6,15,17,30,32 and is consistent with, though somewhat larger than, what is observed in inhouse internal marker-based daily alignment protocol. Reported random setup uncertainty values have significant variation, ranging from 0.9 to 5.1 mm.…”
Section: Methodssupporting
confidence: 58%
See 1 more Smart Citation
“…The 3 mm random setup uncertainty is representative of those used in related literature 4,6,15,17,30,32 and is consistent with, though somewhat larger than, what is observed in inhouse internal marker-based daily alignment protocol. Reported random setup uncertainty values have significant variation, ranging from 0.9 to 5.1 mm.…”
Section: Methodssupporting
confidence: 58%
“…Several authors have studied PTP. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The general finding of these studies is that PTP reduces normal tissue and organ at risk ͑OAR͒ doses while maintaining the same target coverage as marginbased plans.…”
Section: Introductionmentioning
confidence: 89%
“…In all cases, one must keep in mind that radiobiological optimisation of a given treatment plan by means of changing the prescription dose and/or fractionation schedule is not a substitute for good planning in the first place. Ideally, inverse planning based on radiobiological criteria [46,47] could yield true radiobiologically optimal plans which, by definition, could not be further improved in BioSuite.…”
Section: Radiobiological Optimisation Of Radiotherapymentioning
confidence: 99%
“…Baum et al 19 and Sir et al 20 explored objective functions in which each voxel is weighted by a coverage probability, i.e., a probability that the voxel will be included in a target or organ at risk ͑OAR͒ structure. In contrast, Yang et al 21 and Witte et al 22 employed objective functions that are probabilistically weighted functions of biological metrics: Equivalent uniform dose, tumor control probability, and normal tissue complication probability. In simple cases, Unkelbach and Oelfke 24 showed that the above two PTP approaches, i.e., the PWDD and PWOF approaches, are mathematically related.…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors have explored PWOF approaches, including Löf et al, 18 Baum et al, 19 Sir et al, 20 Yang et al, 21 and Witte et al 22 Löf et al 18 proposed a comprehensive adaptive control framework for fractionated radiotherapy that incorporated random setup uncertainties, and demonstrated the occurrence of horns in the resulting dose distributions. This work was pursued by Rehbinder et al, 23 who used fluence modulation to compensate for random errors and couch corrections for systematic errors.…”
Section: Introductionmentioning
confidence: 99%